AKTIVITAS KOMUNIKASI PADA BDRT FIRM DALAM MEMBENTUK KOHESIVITAS - Apriliano, Ricko Alfa (Solidaritas, 2025)
BDRT FIRM is a part of the group of Surakartans supporters who support the Persis Solo team. The BDRT FIRM supporter group has a membership that tends to increase every year. However, the increase in the number of members was accompanied by the number of cases of clashes between BDRT FIRM supporters which also increased. BDRT FIRM supporters appear solid only when there are matches and when there are riots. However, after the match finished they dispersed without being organized. This research aims to determine effective group communication to increase cohesiveness among BDRT FIRM members. This research uses Umdtot theory which shows that group development at BDRT FIRM is formed from the forming element where the introduction of BDRT FIRM members. Storming, here member conflicts begin to occur. Norming, BDRT FIRM members maintain a conducive atmosphere for each other during the match. Performances, forums and anniversary celebration agendas were carried out by BDRT FIRM to build solidarity. This research also shows that group communication in building and increasing the cohesiveness of BDRT FIRM has not been effective. This is because the emotional cohesiveness of several BDRT FIRM members cannot be implemented properly. This is proven by the case where several BDRT FIRM members were involved in riots with fellow Persis Solo supporters and other supporters. The inability of BDRT FIRM members to manage their emotions shows that Emotional Cohesion in BDRT FIRM is not working as it should.